Effect of tranexamic acid on mortality in patients with traumatic bleeding: prespecified analysis of data from randomised controlled trial - Roberts, I; Perel, P; Prieto-Merino, D; Shakur, H; Coats, T; Hunt, BJ; Lecky, F; Brohi, K; Willett, K (BMJ Publishing Group, 2012)
Objectives To examine whether the effect of tranexamic acid on the risk of death and thrombotic events in patients with traumatic bleeding varies according to baseline risk of death. To assess the extent to which current protocols for treatment with tranexamic acid maximise benefits to patients.